Impact of Corporate Social Responsibility on Vietnamese Listed Firm’s Financial Distress Risk - Tran, Thi Xuan Anh; Vũ Thu Thảo (Universitas Muhammadiyah Surakarta, 2024)
The research focuses on examining the impacts of corporate social responsibility (CSR) on the financial distress risk of 50 Vietnamese-listed firms in the plastic-chemical production industry from 2019 to 2023. The research performs some regression models such as OLS, FEM, and REM, then inspect and overcome the defects of the model. The results indicate that social responsibility scores at Vietnamese enterprises tend to increase, especially after the COVID-19 pandemic, and the more businesses comply with CSR criteria, the more likely it will reduce the financial distress risk. However, CSR targets have not been implemented uniformly, posing strategic policies needed to overcome and more strongly promote CSR within Vietnam.